Blood-based analysis of 84 microRNAs identifies molecules deregulated in individuals with type-2 diabetes, risk factors for the disease or metabolic syndrome - Avgeris, M.; Kokkinopoulou, I.; Maratou, E.; Mitrou, P.; Boutati, E.; Scorilas, A.; Fragoulis, E.G.; Christodoulou, M. I. (Diabetes Res Clin Pract, 2020)
AIM: Micro-RNAs (miRNAs) are implicated in insulin-signaling and the development of type-2 diabetes (T2D). Their deregulated expression is mostly described in the pancreas, liver, skeletal muscle, or adipose tissue of diabetic animals. Relevant studies in humans are limited due to difficulties in accessing tissue-biopsies. Though, circulating miRNAs are indicators of organ-specific pathophysiological events and could potentially serve as disease biomarkers. We explored the profile of 84 T2D-related miRNAs in peripheral blood of subjects with or without the disease. METHODS: An RT-qPCR array screening 84 T2D-related miRNAs was applied in samples of T2D (n = 6) versus non-T2D (n = 6) subjects. The deregulated miRNAs were thereafter analyzed in peripheral blood samples of a validation cohort of 40 T2D and 37 non-T2D individuals [16 controls and 21 subjects with metabolic syndrome (Met-S) and/or T2D risk factors (T2D-RF)], using specific RT-qPCR assays. Correlations with clinicopathological parameters and risk factors were evaluated. RESULTS: Subjects with the disease displayed decreased levels of miR-214-3p, miR-24-3p and let-7f-5p, compared to those without. MiRNA levels correlated with serum insulin and HbA1c levels in individuals with T2D or Met-S/T2D-RF, and with higher BMI, dyslipidemia and family history in controls. CONCLUSIONS: Blood levels of miR-214-3p, miR-24-3p and let-7f-5p are down-regulated in T2D- and Met-S/T2D-RF subjects. Future studies are needed to evaluate their potential as disease biomarkers and elucidate the associated tissue-specific pathogenetic mechanisms.
Keywords: Adult; Aged; Animals; Diabetes Mellitus, Type 2/blood/*diagnosis; Down-Regulation; Female; Humans; Insulin-pathway; Male; Metabolic Syndrome/blood/*diagnosis; MicroRNAs/*blood/metabolism; Middle Aged; miRNAs; Peripheral blood; Risk Factors; RT-qPCR array; Type-2 diabetes; Young Adult